PENGARUH GOOD CORPORATE GOVERNANCE DAN KUALITAS AUDIT TERHADAP PRAKTIK MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2017-2019 - Rahmadani, Tania Rickha; Cahyonowati, Nur (Diponegoro Journal of Accounting, 2022)
This study aims to determine the effect of good corporate governance mechanisms and audit quality on earnings management practices in manufacturing companies listed in the Indonesia Stock Exchange on 2017-2019 period. This research uses quantitative research by using multiple linear regression as data analysis. This study uses secondary data in the form of annual financial statements of manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019.The population in this study were all manufacturing companies listed in the Indonesia Stock Exchange on 2017-2019, which recorded 183 companies. The sampling method used in this study was the purposive sampling method, namely by using several criteria so that the researchers obtained a sample of 39 companies.The results showed that audit quality, institutional ownership, independent commissioners, and audit committees had no effect on earnings management practices. While the control variable that affects earnings management practices is the age of the company.